2018
DOI: 10.4103/ijem.ijem_101_18
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine stimulation test: Is single best time point, convenient yet efficacious?

Abstract: Context:To find a single time point during clonidine stimulation test (CST), with highest diagnostic value to rule out growth hormone deficiency (GHD).Settings and Design:This is a retrospective study of 79 CSTs carried out in a tertiary care center in India.Materials and Methods:A cohort of 79 children with unexplained short stature was divided into two groups: GHD and non-GHD. Any one stimulated growth hormone (GH) level >10 ng/mL was used to rule out GHD. Diagnostic accuracy of not only single time points b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
2
5
0
Order By: Relevance
“…The results presented here are consistent with a previous investigation (Bhagwat et al, 2018) that reported a non-signi icant difference between basal GH levels in patients and control. It may be due to the release of growth hormone, which is pulsated with diurnal variation, under a negative feedback autoregulation loop, and may be affected by various factors.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results presented here are consistent with a previous investigation (Bhagwat et al, 2018) that reported a non-signi icant difference between basal GH levels in patients and control. It may be due to the release of growth hormone, which is pulsated with diurnal variation, under a negative feedback autoregulation loop, and may be affected by various factors.…”
Section: Resultssupporting
confidence: 93%
“…and GH3 (after 1.5 hr.) correspond to the results reported in a previous study (Bhagwat et al, 2018) . It may be due to the pulsatile way of GH secretion and the increase after the stimulation.…”
Section: Resultssupporting
confidence: 93%
“…Only somnolence and mild hypotension were observed and did not require oral hydration or saline infusion, as reported by several studies [ 33 , 34 ]. Regarding convenience and cost-effectiveness, another study assessed whether minimizing the sampling points could reduce costs while maintaining the efficacy and sensitivity of the test and concluded that a sample obtained 60 min after clonidine stimulation was the best single sample for ruling out GHD, with 79.5% specificity [ 35 ]. However, Gillis et al reported that the peak indicating GH sufficiency (85.15%) during the CST tended to occur more frequently at typical times (60 min and 90 min) than those indicating GHD (68%) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively long duration of the procedure, up to four hours, is considered a disadvantage of the test [ 5 ]. The clonidine stimulation test (CST) is the preferred test in diagnosing children with GHD [ 6 ]. Clinically, there is no standardized peak time with CST as the GH response peak time could be early or late.…”
Section: Introductionmentioning
confidence: 99%
“…Thakur et al found that the 60 minutes post-CST measurement is the most important to exclude GHD (79.5% specificity). The addition of the 90 minutes raises the test’s specificity to 92.3% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%